Effect of orally administered combination of Caulerpa racemosa and Eleutherine americana (Aubl) Merr extracts on phagocytic activity of macrophage - Ermina Pakki; Rosany Tayeb; Usmar Usmar; Ismul Azham Ridwan; Lukman Muslimin (Wolters Kluwer Medknow Publications, 2020)
Background and purpose: Polysaccharide sulfate is a major active phytochemical constituent of Caulerpa racemosa, whereas the Eleutherine americana (Aubl) Merr has antioxidant properties. The aim of this research was to investigate the combined effect of polysaccharide sulfate that was isolated from C. racemosa and E. americana on the macrophage activity. Experimental approach: The phenolic contents and antioxidant activities of E. americana extracts in water and various ethanol concentrations were studied using the Folin-Ciocalteu and 2,2-diphenyl-1-picryl-hydrazyl- hydrate (DPPH) methods, respectively. Polysaccharide sulfate was isolated from C. racemosa by precipitation method. To assess the macrophage activity, mice were treated orally for 14 days with either a combination of polysaccharide sulfate and E. americana 96% ethanol extract at a specific ratio or with each extract alone. Macrophages were isolated and the phagocytic activity was measured by assessing the ability of the macrophages to phagocytose latex particles and nitric oxide (NO) levels were assessed using a colorimetric assay. Findings / Results: The E. americana crude extract in water exhibited the highest yield (13.04%), compared with the extract in 96% ethanol, which had the highest phenolic content (6.37 ± 0.16 mg/g gallic acid equivalent) and the strongest antioxidant activity (IC50, 22.63 ± 1.09 μg/mL). The combination of extracts, when both extracts were administered at 65:65 mg/kg BW, resulted in the highest increases in phagocytosis activity (62.73 ± 5.77%) and NO levels (16.43 ± 1.37 μmol/L). Conclusion and implications: The results of this study confirmed the non-specific immunostimulant properties of the combination of polysaccharide sulfate and E. americana and justified their use in traditional medicine. The observed increase in macrophage activity appeared to be correlated with the increased ability of mice to fight infection.